2011
DOI: 10.1007/s00779-011-0466-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of mental workload levels during an everyday life office-work scenario

Abstract: Personal and ubiquitous healthcare applications offer new opportunities to prevent long-term health damage due to increased mental workload by continuously monitoring physiological signs related to prolonged high workload and providing just-in-time feedback. In order to achieve a quantification of mental load, different load levels that occur during a workday have to be discriminated. In this work, we present how mental workload levels in everyday life scenarios can be discriminated with data from a mobile ECG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 18 publications
9
127
1
4
Order By: Relevance
“…A statistically significant difference was observed for the features SDNN and RMSSD. Cinaz et al (2013) demonstrated that the features RMSSD and pNN50 decrease significantly with increased MWL. In contrast, a statistically significant difference was observed for HR, LF/HF ratio, and EMG amplitude.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A statistically significant difference was observed for the features SDNN and RMSSD. Cinaz et al (2013) demonstrated that the features RMSSD and pNN50 decrease significantly with increased MWL. In contrast, a statistically significant difference was observed for HR, LF/HF ratio, and EMG amplitude.…”
Section: Discussionmentioning
confidence: 95%
“…Increased demand on available resources can cause human operator overload (Dadashi et al, 2013). In such cases, the operator experiences an extensive level of MWL in his or her daily work without enough time to rest, and health problems such as chronic stress, depression, or burnout can occur (Cinaz et al, 2013), which can influence the worker's performance and well-being (Johnson and Widyanti, 2011). Van Daalen et al (2009) indicated that a mismatch between task demand and the capabilities of the worker can cause work-related stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing within sessions, dfa2 and RPadet were found significantly different between session 1 and 4, while ShanEn between session 3 and 4. Previous studies [15][16][17], showed that as one task's demand increases, HRV becomes more depressed. Added to this, here we found that also on repetitive tasks, there is a depressed HRV over sessions, which is possibly due to an increase in mental workload.…”
Section: Iiiresults and Discussionmentioning
confidence: 99%
“…Mental fatigue can be reflected in physiological features, such as heart rate variability (HRV) and galvanic skin response (GSR). Cinaz et al [4] measured HRV features to quantify the mental workload levels during office-work. Besides, additional subjective difficulty levels were rated by NASA task load index (TLX).…”
Section: Course Difficultymentioning
confidence: 99%